Conceptualising an integrated planning system. (10th May 2005) - Chermack, Thomas J.
This paper explores an innovative approach to planning in organisations based on viewing planning itself as a system. Beginning with an outline of problematic and rigid planning processes, this article advocated for a reconceptualisation of planning itself to accommodate the complex and ever-changing environment in which planning must take place. By using van der Heijden's (1997) strategy paradigms, and Mintzberg and Lampel's (1999) schools of strategy, a heuristic is created for a modular and flexible systems-based approach to planning. Implications for planning practices are considered in light of this novel approach to planning as well as some suggestions for further research.